Therapeutic afucosylated monoclonal antibody and bispecific T-cell engagers for T-cell acute lymphoblastic leukemia. Issue 2 (17th February 2021) - Caracciolo, Daniele; Riillo, Caterina; Ballerini, Andrea; Gaipa, Giuseppe; Lhermitte, Ludovic; Rossi, Marco; Botta, Cirino; Duroyon, Eugénie; Grillone, Katia; Gallo Cantafio, Maria Eugenia; Buracchi, Chiara; Alampi, Greta; et al.
Abstract : Background: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive disease with a poor cure rate for relapsed/resistant patients. Due to the lack of T-cell restricted targetable antigens, effective immune-therapeutics are not presently available and the treatment of chemo-refractory T-ALL is still an unmet clinical need. To develop novel immune-therapy for T-ALL, we generated an afucosylated monoclonal antibody (mAb) (ahuUMG1) and two different bispecific T-cell engagers (BTCEs) against UMG1, a unique CD43-epitope highly and selectively expressed by T-ALL cells from pediatric and adult patients. Methods: UMG1 expression was assessed by immunohistochemistry (IHC) on a wide panel of normal tissue microarrays (TMAs), and by flow cytometry on healthy peripheral blood/bone marrow-derived cells, on 10 different T-ALL cell lines, and on 110 T-ALL primary patient-derived cells. CD43-UMG1 binding site was defined through a peptide microarray scanning. ahuUMG1 was generated by Genetic Glyco-Engineering technology from a novel humanized mAb directed against UMG1 (huUMG1). BTCEs were generated as IgG1-(scFv)2 constructs with bivalent (2+2) or monovalent (2+1) CD3ε arms. Antibody dependent cellular cytotoxicity (ADCC), antibody dependent cellular phagocytosis (ADCP) and redirected T-cell cytotoxicity assays were analysed by flow cytometry. In vivo antitumor activity of ahUMG1 and UMG1-BTCEs was investigated in NSG mice against subcutaneous and orthotopic xenografts of human T-ALL. Results: Among 110 T-ALL patient-derived samples, 53 (48.1%) stained positive (24% of TI/TII, 82% of TIII and 42.8% of TIV). Importantly, no expression of UMG1-epitope was found in normal tissues/cells, excluding cortical thymocytes and a minority (<5%) of peripheral blood T lymphocytes. ahUMG1 induced strong ADCC and ADCP on T-ALL cells in vitro, which translated in antitumor activity in vivo and significantly extended survival of treated mice. Both UMG1-BTCEs demonstrated highly effective killing activity against T-ALL cells in vitro. We demonstrated that this effect was specifically exerted by engaged activated T cells. Moreover, UMG1-BTCEs effectively antagonized tumor growth at concentrations >2 log lower as compared with ahuUMG1, with significant mice survival advantage in different T-ALL models in vivo. Conclusion: Altogether our findings, including the safe UMG1-epitope expression profile, provide a framework for the clinical development of these innovative immune-therapeutics for this still orphan disease.